Law, Business, & Society - Tony McAdams (McGraw-hill, 2012)
In the tenth edition of Law, Business, and Society, Tony McAdams discusses the role of the market, ethics/social responsibility, and the law in regulating the complex relationship between business and the larger society. McAdams examines whether the market and ethics/social responsibility have failed, and if government intervention is needed to maintain a healthy relationship between business practice and society’s general welfare. The text serves as a general introduction to the legal system, including chapters on constitutional law, the common law of contracts and torts, and employment law. The closely written narrative, edited law cases, contemporary vignettes from daily life and an abundance of thought-provoking questions help convey key points. In addition, Law, Business, and Society precisely conforms to AACSB International accreditation expectations